Modulation of physical exercise intensity in motor‐cognitive training of adults using the SKILLCOURT technology - Gülsa Erdogan; Bettina Karsten; Lutz Vogt; Andreas Mierau; Thorben Hülsdünker (Physiological Reports)
Abstract Motor‐cognitive training and exergaming often only reach low‐to‐medium intensities that limits their training efficiency. This study evaluated the physiological profile of different exercises on a novel motor‐cognitive training technology designed to cover a broad range of exercise intensities. Twenty‐six healthy trained adults (17 males, 23.7 ± 3.8 years) performed five motor‐cognitive training tasks on the SKILLCOURT technology. Oxygen consumption (VO2), heart rate (HR), blood [lactate], perceived physical exertion (RPE) responses, and metabolic equivalent (MET) were assessed and compared to an incremental treadmill ramp test determining the maximal oxygen consumption (VO2max) and maximal heart rate (HRmax). Computer‐based cognitive training served as control condition. Motor‐cognitive exercises reached a higher %VO2max and %HRmax levels when compared to computer‐based training (p < 0.001). Average intensity varied significantly between motor‐cognitive tasks, with %VO2max ranging from 22% to 81% (p < 0.001), %HRmax from 49% to 89% (p < 0.001), METs from 3.57 to 13.37 (p < 0.001), blood [lactate] from 0.93 to 7.81 mmol·L−1 (p < 0.001), and RPE from 8.5 to 16.4 (p < 0.001). Motor‐cognitive training covers a wide range of exercise intensities. This supports individual training subscription and allows high‐intensity training to facilitate cardio‐vascular adaptations and neural plasticity.